THE COMPARATIVE STUDY OF STUDENTS' LEARNING STYLE ON THEIR ACHIEVEMENT IN READING SKILL - Muhamad Sofian Hadi; Lidiyatul Izzah; Mutiara Nurul Humaira Hidayat (STKIP Siliwangi, 2021)
The purpose of this study is to know the difference of students’ learning style on their English achievement in reading skill of the second grades students of SMPI An-Nuqthah Cipete in Tangerang, Banten. This study uses a causal comparative research design and purposive sampling technique. The sample of this study is 34 second grade students of SMPI An-Nuqthah. They are divided into three types of learning style: visual learning style, auditory learning style and kinesthetic learning style. A questionnaire is used to determine each students’ learning style. Students’ learning style and their English achievement in reading skill were analyzed by using percentage and bifilar linear regression analysis. The result of this study revealed that most of students have a visual learning style (50% from 34 students). The adjusted R score = 51.8%, which means that the learning style contributes about 51.8% to the English reading skill of the second grades students of SMPI An-Nuqthah, and another 48.2% are affected by other factors and need further study. According to the results, the students' visual learning style t-test is higher than the value of the t-table. The conclusion of this research is that visual learning style is the best way to make reading comprehension easier.